The Ethnography of Dakwah in Bontang City - Syamsuri, Syamsuri; Multi Ali; Minannur (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2024)
The ethnic diversity of the archipelago has succeeded in confirming and transforming dakwah in Bontang City. Professional struggles in the industrial world brought about the ethnological civilization of dakwah, which provided a spirit of independence in the ijtihad of the ustaz and ulama to establish Bontang as the City of Tahfiz. The struggle to make the Al-Quran the main guideline for technological and industrial guidance gave birth to creativity in preaching to do good and prevent evil. The ethnographic research method, using a Participatory Action Research (PAR) approach, succeeded in explaining dakwah activities in Bontang City by displaying ethnic diversity but within the framework of the Bhinneka Tunggal Ika ideology. Community figures were encouraged to bring ustaz and ulama from the islands of Sulawesi and Java to come to preach in Bontang City, so that there was a diversity of preaching institutions with their respective ethnic variations and slogans.